THE ROLE OF MOTIVATION AND JOB SATISFACTION FOR THE PERFORMANCE OF POTTERY CRAFTSMEN IN BANTEN - Heri Sapari Kahpi; Urfanul Aulia; Willy Nurhayadi; Muhamad Dadi Priadi (SEAN Institute, 2023)
This study aimed to determine the effect of motivation to the craftsmen’s performance, motivation towards job satisfaction, and the effect of job satisfaction on craftsmen performance. This research is included in the type of causal research. The population in this study were all MSMEs pottery craftsmen in Bumi Jaya Village, Ciruas District, Serang Regency, Banten. Samples were taken using non-probability sampling of 78 pottery craftsmen. Data were collected using a questionnaire, then analyzed using SEM analysis with the help of SmartPLS. The results of this study is indicating that motivation has a positive and significant effect on the performance of craftsmen, craftsmen motivation has a positive and significant effect on job satisfaction, job satisfaction has a positive and significant effect on craftsmen performance and motivation has a positive and significant effect on performance through job satisfaction.